СКВОЗНЫЕ ПРОЦЕССЫ ЗАГОТОВКИ ПИЩЕВОГО СЫРЬЯ И ПРОИЗВОДСТВА ИЗ НЕГО ФУНКЦИОНАЛЬНЫХ ПРОДУКТОВ ДЛЯ ПОВЫШЕНИЯ ПРОДОВОЛЬСТВЕННОЙ БЕЗОПАСНОСТИ СЕВЕРНЫХ РЕГИОНОВ РОССИИ - Shegelman I. R., Vasilyev A. S., Shchukin P. O. (Science, education, society: trends and prospects, 2019)
it is shown that the processes of formation of import-substituting end-to-end technologies for the harvesting of food raw materials and its production of functional foods from it, along with the development of the agro-industrial sector in the regions of the European North, are the most important factors for improving the food security of the population living in these regions.
Keywords: северные регионы России; производство; продовольственная безопасность; заготовка; сквозные процессы; функциональные пищевые продукты; functional foods; food security; the northern regions of Russia; through the processes of harvesting and production